PELAKSANAAN TEKNIK EVALUASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ahmad Sarifuddin (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2020)
This paper aims to determine the implementation of evaluation techniques for Islamic religious education. This paper uses a qualitative approach and literature study methods. Based on the results of the discussion, evaluation consists of measurement and assessment. In the context of learning, evaluation has a very important and strategic position, because it  included in the steps or learning. The goal is to determine the effectiveness and efficiency of the learning system. In general, the principle of evaluation consists of continuity, comprehensive, fair, objective, cooperative, and accountability. In terms of its type, learning evaluation consists of evaluation of planning, development, monitoring, impact, efficiency, and comprehensive programs. Judging from the object, learning evaluation includes input, transformation, and output. As for the subject is educators, officers who have been coached, even students can evaluate they-self. From a technical point of view, it consists of tests and non-tests. The implementation of the Islamic Religious Education learning test technique must be carried out continuously, comprehensively, and integrated. Thus, Islamic education educators must be able to evaluate the development of students including aspects, aqliyah, qolbiyah, dan amaliyah.